Of markets and middlemen: the role of brokers in Ethiopia - Gabre-Madhin, Eleni Zaude (International Food Policy Research Institute, 1999)
Using survey data on traders and brokers in the Ethiopian foodgrain market, this paper reveals that the brokerage institution is critical to market performance in that it enables traders to circumvent the commitment problem of long-distance trade with unknown partners. In the absence of grain standardization, public information, and legal contract enforcement, brokers act as inspectors and guarantors of each transaction. The paper analyzes the sources of commitment failure, the role and functions of brokers and the extent of brokerage use by brokers, and argues that agency relations are not based on ethnicity, depend on effective reputation rather than trust, and are structured in an incentive-compatible manner.